2022
DOI: 10.1186/s13046-022-02437-8
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 promotes NSCLC carcinogenesis through translationally and transcriptionally activating DLAT-mediated glycolysis reprograming

Abstract: Background Airborne fine particulate matter (PM2.5) has been associated with lung cancer development and progression in never smokers. However, the molecular mechanisms underlying PM2.5-induced lung cancer remain largely unknown. The aim of this study was to explore the mechanisms by which PM2.5 regulated the carcinogenesis of non-small cell lung cancer (NSCLC). Methods Paralleled ribosome sequencing (Ribo-seq) and RNA sequencing (RNA-seq) were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 61 publications
4
32
0
Order By: Relevance
“…Over expression of glycolytic gene DLAT, which promoted glycolysis but suppressed acetyl-CoA production and enhanced the malignancy of non-small cell lung cancer (NSCLC) cells. Clinically, high expression of DLAT was positively associated with tumor size, poorer prognosis, and SUVmax values of 18F-FDG-PET/CT scans in patients with NSCLC ( Chen et al, 2022 ). GLS the first enzyme in glutaminolysis, is overexpressed in ibrutinib-resistant mantle cell lymphoma (MCL) cells, and that its expression correlates well with elevated glutamine dependency and glutaminolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Over expression of glycolytic gene DLAT, which promoted glycolysis but suppressed acetyl-CoA production and enhanced the malignancy of non-small cell lung cancer (NSCLC) cells. Clinically, high expression of DLAT was positively associated with tumor size, poorer prognosis, and SUVmax values of 18F-FDG-PET/CT scans in patients with NSCLC ( Chen et al, 2022 ). GLS the first enzyme in glutaminolysis, is overexpressed in ibrutinib-resistant mantle cell lymphoma (MCL) cells, and that its expression correlates well with elevated glutamine dependency and glutaminolysis.…”
Section: Discussionmentioning
confidence: 99%
“…We defined three common DEGs between NASH and HCC. DLAT, or dihydrolipoamide S-acetyltransferase, has been reported to mediate glycolysis reprogramming in non-small cell lung cancer [ 36 ]. It is also considered to be one of the key proteins regulating cuproptosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…DLAT (dihydrolipoamide S-acetyltransferase) is expressed in mitochondria which involved in cell glycolysis. A number of malignancies, including lung cancer ( 22 ), gastric cancer ( 23 ) and colon cancer ( 24 ), have been associated with high expression of DLAT in various tumors. These studies suggested a potential role of DLAT in abnormal cuproptosis metabolism in LUAD.…”
Section: Discussionmentioning
confidence: 99%